Reconfiguração de sistemas de distribuição operando em vários níveis de demanda através de uma meta-heurística de busca em vizinhança variável - Possagnolo, Leonardo Henrique Faria Macedo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The distribution network reconfiguration problem consists in determining the radial to- pology, that can be obtained by opening and closing sectionalizing switches (normally closed switches) and tie switches (normally open switches), so that an objective is achieved, commonly loss minimization, load balancing, voltage levels improvement or fault isolation. Furthermore, the optimal topology must satisfy operational constraints, such as voltage levels on nodes and current magnitude on circuits. The model for this problem is a mixed-integer nonlinear pro- gramming problem, non-convex and hard to solve by classical optimization techniques, besides, this problem presents the combinatorial explosion phenomenon. This work presents methodol- ogies, based on the variable neighborhood search metaheuristic, to solve the distribution net- work reconfiguration problem with variable demand and fixed topology, which aims in finding only one optimal topology to operate on the various load levels during a period. The considered objective is the reduction of the cost of energy losses. Four variable neighborhood search algo- rithms were developed: Basic Variable Neighborhood Search (BVNS), Variable Neighborhood Descent (VND), Reduced Variable Neighborhood Search (RVNS) and General Variable Neigh- borhood Search (GVNS). All programs were implemented in FORTRAN. The proposed algo- rithms were tested with the 33, 84, 136, 415 and 10477-node systems. The results were com- pared with the best-known solutions presented in specialized literature and the solutions ob- tained from an optimization model, written in AMPL and solved with commercial solver CPLEX

O problema da reconfiguração de sistemas de distribuição de energia elétrica consiste em determinar a topologia radial, que pode ser obtida por meio da abertura ou fechamento de chaves de seccionamento (normalmente fechadas) e de ligação (normalmente abertas), de forma que um objetivo seja atingido, geralmente a minimização das perdas, balanceamento das cargas, melhoria dos níveis de tensão ou isolamento de faltas. Além disto, a topologia ótima deve cum- prir com restrições operacionais, como o limite de tensão nas barras e os limites de correntes nos circuitos. O modelo deste problema é de programação não linear inteira mista, não convexo e de difícil solução através de técnicas clássicas de otimização, além disto, este problema apre- senta o fenômeno da explosão combinatória. Neste trabalho são apresentadas metodologias, baseadas na meta-heurística de busca em vizinhança variável, para resolver o problema da re- configuração de sistemas de distribuição de energia elétrica considerando vários níveis de de- manda e topologia fixa da rede, que visa encontrar uma única topologia ótima para operar nos vários níveis de demanda de um período. O objetivo considerado é a minimização do custo das perdas de energia. Foram desenvolvidas quatro formas do algoritmo de busca em vizinhança variável: Basic Variable Neighborhood Search (BVNS), Variable Neighborhood Descent (VND), Reduced Variable Neighborhood Search (RVNS) e General Variable Neighborhood Search (GVNS). Todos os programas foram escritos em linguagem FORTRAN. Os algoritmos propostos foram testados com os sistemas de 33, 84, 136, 415 e 10477 barras. Os resultados foram comparados com os existentes na literatura especializada e os obtidos pela resolução de um modelo de otimização, escrito em linguagem AMPL e resolvido com o solver comercial CPLEX
Keywords: Energia elétrica - Distribuição; Sistemas de energia eletrica; Programação heuristica; Electric power distribution